Athletic retirement: factors contributing to sleep and mental health problems - Montero, A.; Baranoff, J.; Adams, R.; Drummond, M. (Frontiers in Psychology, 2024)
Introduction: The aim of this investigation was to determine which factors were associated with symptoms of sleep and mental health disorders in former athletes.